Structure analysis of multi-component pastes – The effect of water distribution on the rheological properties. (December 2022) - Cäcilie Möller, Anna; Lie-Piang, Anouk; Bian, Ting; van der Padt, Albert; Jan van der Goot, Atze
Graphical abstract: Highlights: Polymer blending law describes binary pea ingredient blends' fraction behavior well. Blend properties are described through water distribution and blend structure. Relative water uptake relates to the phase strength in a blend. Isolate-based models can describe multi-component ingredients' microstructure. Abstract: Techno-functional properties of multi-component blends and ingredients are determined by the contribution of each ingredient and the water distribution between those ingredients in the blends. However, ingredients can consist of multiple components, which should be considered to better understand the properties of ingredients and blends thereof. Recently, empirical models were used to describe the viscosity of mildly refined ingredient blends. While many compositions were described well by the empirical models, blends with high fiber contents were not predicted sufficiently well. Therefore, in this research, the multi-component blends of commercial pea protein, pea starch, and pea fiber isolates were investigated on their rheological properties as a function of dry matter content. The same properties were then measured for blends of two of these isolates mixed in different ratios. From the rheological experiments, estimations of the water distribution were made with the polymer blending law. The results were compared with CLSM images. A quantitative analysis of the CLSM images mostly confirmed the model outcomes. The isolate ratio could describe the isolate blends sufficiently well, meaning that it was not necessary to know the exact compositions of the ingredients. It was concluded that changes in meso -structure of the blends, for example a phase transition at high fiber contents, caused the lower predictability by the recently published empirical viscosity models. This study demonstrates that the water distribution in multi-component blends plays a crucial role for their viscoelastic properties and the contribution of the individual isolates and components. Moreover, these polymer blending laws that include water distribution provide extra mechanical insights into the fraction behavior in multi-component blends.